PHYSICAL EDUCATION - PHYSICAL CULTURE. TWO MODELS, TWO DIDACTIC - Manuel Vizuete Carrizosa (Federación Extremeña de Balonmano; University of Extremadura, 2014)
Physical Education is currently facing a number of problems that are rooted in the identity crisis prompted by the spread of the professional group, the confrontation of ideas from the scientific community and the competing interests of different political and social areas, compared to which physical education has failed, or unable, to react in time. The political and ideological confrontation that characterized the twentieth century gave us two forms, each with a consistent ideological position, in which the body as a subject of education was understood from two different positions: one set from the left and communism and another, from Western democratic societies. The survival of these conflicting positions and their interests and different views on education, in a lengthy space of time, as a consequence threw two teaching approaches and two different educational models, in which the objectives and content of education differ , and with them the forms and methods of teaching. The need to define the cultural and educational approach, in every time and place, is now a pressing need and challenge the processes of teacher training, as responsible for shaping an advanced physical education, adjusted to the time and place, the interests and needs of citizens and the democratic values of modern society.